Pelayanan Konseling Berbasisi Tugas Perkembangan - Rahma Wira Nita; Wira Solina (Jurnal Counseling Care, 2019)
Students of the Guidance and Counseling Study Program (BK) of STKIP PGRI West Sumatra as prospective conselor who are required to have independence in the field of employment development to improve accuracy, development, so as not to change the phase and subsequent developments. To welcome this, it is necessary to disclose the victory of student assignments through the Development Task Application (ATP). This research was conducted to reveal and analyze the development of students' assignments as candidates for conselor through the Development Instrument application. The type of research is quantitative descriptive with BK student research in 2016 which was arrested by 63 students. The collected data was developed with the Developmental Task Application. The results of the study, in general, the results of the 2016 BK students' ITP by following the Level of Careful Development were that students acted on internal values, were responsible for the choices taken to be carried out and the choices taken were future-oriented and long-term. Creation with a careful level on aspects, religious foundation, intellectual maturity, responsible awareness, career insight and preparation and self-preparation for family life. To improve the other six aspects, it was designed the action of ITP-based Counseling Service Plan Program